Re-adjustment of precise levelling network and analysis of the orthometric height for Brunei Darussalam - Aierna Bakar 632561; Kamaludin Mohd. Omar supervisor 235418; Fakulti Geoinformasi dan Harta Tanah 555724 (2011)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2011